2003
DOI: 10.2151/jmsj.81.1243
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of a Mesoscale Convective System in a Baiu-Frontal Depression Generated in the Downstream Region of the Yangtze River

Abstract: A Baiu-frontal meso-a-scale depression was generated on 18 June 2001 in the mesoscale observational region, which was located in the downstream region of the Yangtze River. Based mainly on the data collected in this observation, we analyze the three-dimensional structure of a meso-a-scale convective system. We describe this structure and discuss the evolution of Baiu-frontal convective systems near the east coast of the continent.This convective system was composed of several meso-b-scale convective groups, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Shear at low-to-medium levels has been reported by Parker and Johnson (2004) as an important factor in the maintenance of convective systems, which may be a reason for the extended lifetime of NMαCS. Such a vertical wind shear was also observed in past studies on a convective system along Meiyu/Baiu frontal regions (Ogura et al, 1985;Ishihara et al, 1995;Yamada et al, 2003;Zhou, 2009). They described that convective systems formed on the shear line, a southwesterly jet was prevalent in the low troposphere.…”
Section: Three-dimensional Structure and Development Processes Of Consupporting
confidence: 73%
See 1 more Smart Citation
“…Shear at low-to-medium levels has been reported by Parker and Johnson (2004) as an important factor in the maintenance of convective systems, which may be a reason for the extended lifetime of NMαCS. Such a vertical wind shear was also observed in past studies on a convective system along Meiyu/Baiu frontal regions (Ogura et al, 1985;Ishihara et al, 1995;Yamada et al, 2003;Zhou, 2009). They described that convective systems formed on the shear line, a southwesterly jet was prevalent in the low troposphere.…”
Section: Three-dimensional Structure and Development Processes Of Consupporting
confidence: 73%
“…This study utilised Doppler radar, which provides datasets with high spatial and temporal resolutions of the internal structure of precipitation. In the past, dual-Doppler radar observations have provided in-depth information on structures of the meso-α and meso-β scales, including their development in monsoon frontal systems (Yamada et al, 2003;Moteki et al, 2004;Geng et al, 2004). You et al (2010) proved that deep warm-air advection (WAA) supports the maintenance of a convective system for a longer time and results in greater rain intensity, producing drops of larger sizes.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the severe weather events (such as strong wind and heavy rainfall) induced by these vortices in the East China Sea and Yellow Sea have become a significant problem for the shipping, fishing, and energy exploration industries of Northeast Asian countries, especially China. Although there are a certain number of studies focused on eastward-moving vortices (e.g., Yamada et al, 2003;Sun et al, 2010), the details of the move-off-shore vortices are still unclear due to the lack of observations at sea and the short lifespans of the vortices in general cases (Geng, 2008). Therefore, the purpose of this study is to investigate the evolution of the move-off-shore MBFMV and compare the maintenance mechanisms of the vortex under different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed large scale characteristics of MBFD (e.g., Yoshizumi 1977;Akiyama 1984), the evolution of MBFD from cloud clusters (e.g., Ninomiya and Akiyama 1971;Ninomiya et al 1981), precipitation features associated with MBFD (e.g., Ninomiya 1978;Ninomiya and Shibagaki 2003), and the internal kinematic structure of MBFD from the Doppler radar observation (e.g., Yamada et al 2003). Recently, a nonhydrostatic model has been used to illustrate processes related to the development of MBFD (Tagami et al 2007).…”
Section: Introductionmentioning
confidence: 99%